Understanding Your Child's Temperament - Diana Converse; Donna Davis (EDIS)
FAR0077, a 2-page transcript of the Family Album Radio Program broadcast by Diana Converse and Donna Davis, describes nine behavior traits that are present at birth and can be used by parents to understand their children’s temperaments. Published by the UF Department of Family Youth and Community Sciences, March 2009.